Assessing the Perceived Training Needs of Farm Women on Modern Crop Technologies in Jhansi District - Yash Pateriya; A.K Bharti; Yogesh Kumar; Kumar Sonu (Indian Journal of Extension Education, 2025)
The study assesses the perceived training needs of farm women in modern crop production technologies, situated in the complex agro-economic landscape of Jhansi district. Despite their critical role in agriculture, women farmers often face barriers to accessing technical knowledge, which limits their productivity and empowerment. Using a descriptive survey design with a sample of 120 farm women from Mauranipur block, this research employed a multi-stage sampling technique and a structured interview schedule to collect data during 2022-23. The results reveal that the highest training needs were in crop storage (WS=2.23) and cattle production (WS=2.23), followed by weed control (WS=2.18) and improved crop varieties (WS=2.18). The majority of women (73.34%) fell into the medium training-need category, indicating a widespread demand for skill upgradation. Psychological variables, particularly scientific orientation (r=0.548) and risk orientation (r=0.498), emerged as the strongest predictors of training need, surpassing most socio-economic factors. Education, landholding, and income also showed significant positive correlations. These findings underscore the necessity of designing gender-responsive, needs-based extension programs that not only address technical skill gaps but also foster psychological readiness for innovation, thereby enabling more inclusive and sustainable agricultural development.